(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objectives: The current study examined the widespread use of whole and limited Edentulism concerning gender, age, and educational attainment among adults and older residents of Saudi Arabia. We can encourage oral hygiene with the help of baseline knowledge about Edentulism. Methods: In 2018–2019, several dental care facilities located throughout Saudi Arabia participated in a cross-sectional stratified cluster study. A total of 618 subjects between the ages of 35 and 74 were chosen through practical sampling, and after collecting data on edentulism, a clinical examination was conducted. Results: Males made up 350 (56%), and females made up 262 (43%) of the sample as a whole. According to the analysis of edentulism, most of the 427 subjects (69 per cent) had one or more missing teeth. A total of 2.6 points, 6 per cent of these subjects were denuded entirely, making up 1.8 points, 8 per cent of the sample as a whole. Conclusion: Grown-up patients commonly have one or more teeth absent, and elderly patients are more likely to be completely edentulous. Edentulism had a negative correlation with visiting a dental office.